Human Rights Fulfilment in Lapindo Mudflow-Affected Communities: A Maqāsid Fulfilment Index Approach - Arie Baskhoro; Thi Phuoc Lai Nguyen; Amany Lubis (AHKAM : Jurnal Ilmu Syariah, 2026)
Long-term recovery after the Lapindo mudflow cannot be assessed solely by technical rehabilitation, relocation, compensation, or service restoration. This study analyzes human rights fulfillment among affected Muslim communities using a minimum obligation framework based on maqāṣid al-sharī‘ah. The five dimensions (religion, life, intellect, family, and wealth) are expressed as 25 rights indicators within the Maqāṣid Fulfilment Index (MFI). Data from 300 respondents in Tanggulangin, Jabon, and Porong were analyzed using normalized scoring, the Kruskal-Wallis test, stakeholder accountability mapping, and normative legal benchmarking. Results show moderate but uneven fulfillment. Life and intellect are relatively stronger, while wealth, compensation, legal aid, documentation, and religious and family support remain weak. This study introduces a measurable tool to link rights deficits with vulnerability, institutional accountability, and recovery pathways in long-term disaster governance. It reframes recovery as a question of measurable protection, responsibility, and remedy over time.   Abstrak Pemulihan jangka panjang pasca letusan lumpur Lapindo tidak dapat dinilai hanya melalui rehabilitasi teknis, relokasi, kompensasi, atau pemulihan layanan. Studi ini menilai pemenuhan hak asasi manusia komunitas Muslim terdampak melalui kerangka kewajiban minimum berbasis maqāṣid al-sharī‘ah. Lima dimensi yang diukur, yaitu agama, jiwa, akal, keluarga, dan harta, dioperasionalkan menjadi 25 indikator hak dalam Maqāṣid Fulfilment Index (MFI). Data dikumpulkan dari 300 responden di Tanggulangin, Jabon, dan Porong, lalu dianalisis melalui skor ternormalisasi, uji Kruskal Wallis, pemetaan akuntabilitas pemangku kepentingan, dan pembandingan norma hukum. Hasil menunjukkan pemenuhan sedang tetapi tidak merata. Jiwa dan akal relatif lebih kuat, sedangkan harta, kompensasi, bantuan hukum, dokumentasi, serta dukungan agama dan keluarga masih rapuh. Studi ini berkontribusi melalui instrumen terukur yang menghubungkan defisit pemenuhan hak dengan distribusi kerentanan, akuntabilitas institusional, dan jalur pemulihan dalam tata kelola bencana jangka panjang. Dengan demikian, pemulihan dibaca sebagai persoalan perlindungan, tanggung jawab, dan remedy yang terukur dari waktu ke waktu.